2002
DOI: 10.1038/4151011a
|View full text |Cite
|
Sign up to set email alerts
|

High mixing rates in the abyssal Southern Ocean

Abstract: Mixing of water masses from the deep ocean to the layers above can be estimated from considerations of continuity in the global ocean overturning circulation. But averaged over ocean basins, diffusivity has been observed to be too small to account for the global upward flux of water, and high mixing intensities have only been found in the restricted areas close to sills and narrow gaps. Here we present observations from the Scotia Sea, a deep ocean basin between the Antarctic peninsula and the tip of South Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
107
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 26 publications
2
107
0
2
Order By: Relevance
“…A high-resolution model clearly showed that the link between surface-intensified eddying geostrophic flows, bottom-enhanced velocities, topographic internal gravity waves, and energy dissipation is of primary importance for the energetic of the Antarctic Circumpolar Current (Nikurashin et al 2013). Observations of turbulent mixing also support this scenario in the Southern Ocean (Heywood et al 2002;Naveira Garabato et al 2004;Sloyan 2005;Sheen et al 2013).…”
mentioning
confidence: 68%
“…A high-resolution model clearly showed that the link between surface-intensified eddying geostrophic flows, bottom-enhanced velocities, topographic internal gravity waves, and energy dissipation is of primary importance for the energetic of the Antarctic Circumpolar Current (Nikurashin et al 2013). Observations of turbulent mixing also support this scenario in the Southern Ocean (Heywood et al 2002;Naveira Garabato et al 2004;Sloyan 2005;Sheen et al 2013).…”
mentioning
confidence: 68%
“…As previously documented with other observations, the South China Sea ) and Hawaiian Ridge ) both have diffusivities as high as K ; 10 23 m 2 s 21 . Elevated diffusivities are also found south of Australia and in the Southern Ocean east of South America (Heywood et al 2002). Equatorial regions also show enhanced diffusivity, which has been linked to diurnal deep-cycle turbulence, tropical instability waves, and instabilities of the Equatorial Undercurrent (Moum et al 2009), processes that are likely confined to the upper ocean.…”
mentioning
confidence: 93%
“…High mixing rates observed or inferred to prevail in the deep Southern Ocean (Olbers and Wenzel 1989, Heywood et al 2002, Naveira Garabato et al 2004, Sloyan 2005, Kunze et al 2006 are 716 often suggested to contribute prominently to the diabatic closure of the abyssal overturning circulation (Ito andMarshall 2008, Nikurashin andFerrari 2013). However, inverse estimates and 718 model simulations generally show an increase of the maximum northward abyssal flow as AABW crosses the ACC (e.g., Lumpkin and Speer 2007, Jayne 2009, Melet et al 2014, 720…”
mentioning
confidence: 99%